2024
DOI: 10.1021/acs.chemmater.3c03321
|View full text |Cite
|
Sign up to set email alerts
|

19F MRI In Vivo Monitoring of Gelatin-Based Hydrogels: 3D Scaffolds with Tunable Biodegradation toward Regenerative Medicine

Kristyna Kolouchova,
Vit Herynek,
Ondrej Groborz
et al.

Abstract: Gelatin-based hydrogels emerged as promising biodegradable cell-compatible 3D-printable materials with tunable mechanical properties that serve tissue engineering and applications in regenerative medicine. Nevertheless, these materials are very challenging to monitor in vivo, which has hampered the further development of these materials and their translation into clinical practice. To overcome this limitation, we designed a crosslinked 3D-printable gelatin-based hydrogel endowed with poly[N-(2,2-difluoroethyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…Szabó et al previously reported on the crosslinking efficiency of gel-MA-AEMA in the context of DLP processing, which resulted in 100% crosslinking efficiency regarding the -MA moieties and 96% for the -AEMA functionalities. Therefore, our findings are in line with previous reports [ 3 , 4 , 48 ].…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…Szabó et al previously reported on the crosslinking efficiency of gel-MA-AEMA in the context of DLP processing, which resulted in 100% crosslinking efficiency regarding the -MA moieties and 96% for the -AEMA functionalities. Therefore, our findings are in line with previous reports [ 3 , 4 , 48 ].…”
Section: Resultssupporting
confidence: 94%
“…The swelling ratio of the gel-MA-AEMA-F hydrogels was 4.8 ± 0.37 for 2D film, which suggests a significant decrease in the swelling capacity of the gel-MA-AEMA component upon supplementing it with a small crosslinker molecule, herein DFEA ( p < 0.0001). The results are in line with our previous study, where the addition of DFEA significantly decreases the swelling ratio of the modified gelatins [ 3 , 4 ]. The reason for this decrease in the SR is due to the hydrophobic nature of the PDFEA linkers and offers the potential to provide superior CAD/CAM mimicry to the hereby developed gel-MA-AEMA-F biomaterial inks.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations